The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/s1047951118000641
|View full text |Cite
|
Sign up to set email alerts
|

Patent ductus arteriosus in preterm infants born before 30 weeks’ gestation: high rate of spontaneous closure after hospital discharge

Abstract: A total of 593 infants met the inclusion criteria, and patent ductus arteriosus was diagnosed in 317 (53.4%). Among them, 283 (89.3%) infants had haemodynamically significant patent ductus arteriosus, with pharmacological closure achieved in 228 (80.6%) infants and surgical ligation performed in 20 (7.1%). Follow-up at 24 months was available for 39 (81.3%) of 48 infants with patent ductus arteriosus at the hospital discharge: 36 (92.3%) underwent spontaneous closure, two (5.1%) underwent surgical ligation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
(49 reference statements)
3
15
6
Order By: Relevance
“… 10 , 17 This is important, as disparate results in this high-risk population should promote equipoise regarding enrollment in randomized trials to resolve the question of who to treat, using which criteria, and when. Consistent with other studies, 18 they reported a high rate of ductal closure among infants discharged with PDA, affirming that spontaneous closure after discharge can generally be expected. Finally, they reported that no infants with PDA at discharge developed pulmonary hypertension, for which they were carefully monitored.…”
supporting
confidence: 89%
“… 10 , 17 This is important, as disparate results in this high-risk population should promote equipoise regarding enrollment in randomized trials to resolve the question of who to treat, using which criteria, and when. Consistent with other studies, 18 they reported a high rate of ductal closure among infants discharged with PDA, affirming that spontaneous closure after discharge can generally be expected. Finally, they reported that no infants with PDA at discharge developed pulmonary hypertension, for which they were carefully monitored.…”
supporting
confidence: 89%
“…22 Despite differences in both PDA sizes and follow-up period, our cohort of infants was in agreement with other studies that report similar median GA and birth weight, hence making our findings comparable. 7,[16][17][18] The incidence of NEC in our study was 10% which is high compared to 2-8% in other premature infants. [23][24][25] In addition, 35%…”
Section: Bold Indicates Significant P-valuescontrasting
confidence: 45%
“…Twenty articles were included in group 2 (GA < 30 weeks and/or BW < 1,250 g) (11,(21)(22)(23)(24)(25)(26)(27)(28)(29)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). The median of the reported mean or median GA of the 2,980 patients in group 2 was 28.0 (range 26.2-28.8).…”
Section: Subgroup Analysismentioning
confidence: 99%